Family Harmony in Implementation Of Pohutu Moponika Tradition in Gorontalo City in The Perspective of al-Thufi’s Maslahah - Nency Dela Oktora; Muhammad Yusuf Putra; Nurul Mahmudah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This study is aimed at discussing the system and procession of indigenous Mohammed Moponika marriage in creating the value of family harmony in Gorontalo City based on Al-Thufi’s perspective on maslahah. This study used in this research is the type of field research with descriptive method of phenomenological approach. The results of this study conclude that in the traditional procession of the Pohutu Moponika Marriage accommodates many aspects of benefit in an effort to give birth to a harmonious family. The value of benefit intended for the Pohutu Moponika tradition is to gain or gain benefits and reject harm in order to maintain goals syara‘. Although it is not regulated in the texts and does not seem to be in accordance with the provisions of the texts, the customary process of the Pohutu Moponika Marriage in Gorontalo does not aim to destroy religion. On the contrary, it is actually intended for the benefit of the bride and groom so that they can navigate a harmonious domestic life. Therefore, it is included in the maslahah category in accordance with the concept of al-Thufi. Basically, Allah Swt establishes the rules of command and prohibition that are essentially only intended for the good and benefit of humans.